New mothers' experiences of the urban environment with their preterm infants involve complex social, emotional and psychological processes. (26th January 2017) - Gullino, Silvia; Kaiser, Anthony; Khan, Hammad; Phillips, Aisling; Elwin, Alice; Edwards, AD
Abstract: Aim: Studies have explored how mothers and premature babies make the transition from a neonatal unit (NNU) to home, but little is known about how mothers cope with urban life with a vulnerable baby. This controlled trial investigated how first‐time mothers with singleton preterm babies handled that experience in the first few months after discharge from a NNU, compared to the first‐time mothers of healthy, singleton term‐born infants. Methods: This parent‐led, qualitative study was carried out in London, UK, from 2013 to 2015 and used diaries and walking interviews with researchers. Thematic network analysis was performed to provide insights into the experiences of these 19 mothers. Results: The two groups had similar experiences and needs in the urban environment, and these common experiences of city life shaped their new identities as mothers. However, the mothers of preterm babies had difficulties developing supportive relationships and seeking affirming social environments. Conclusion: This study highlights what the mothers of preterm babies experienced in the first few months after their infant was discharged from hospital. It stresses the need to understand the complexity of the mothers' social, emotional and psychological processes when they make the transition from home to visit the city with a vulnerable baby.